Purifying a house from blood: a Hittite ritual for the ancient gods (CTH 446) - Trameri, Andrea (Lockwood Press, 2022)
Manuscripts, dating, and palaeography. Tablets and archaeological context -- Dating: content, language, and palaeography -- Conclusions -- Content of the purification ritual CTH 446. Hittite rituals and the conception of purity -- Divine participants -- The composite background of CTH 446 in historical context -- Ritual matter and goal -- Ritual structure and performance -- Text edition. Transliteration and translation -- Philological notes and commentary -- CTH 446 in context: construction and content of Hittite rituals. Purification rituals and the role of the ancient gods -- Distinctive ritual practices and formal components -- Purification rituals for buildings -- Symbology of blood and "blood rituals" -- Mythological content -- Conclusions -- Nature and goals of CTH 446. Structure and content: the "compilation" hypothesis -- Discussion -- Is CTH 446 a literary text?. Unicity of CTH 446? -- CTH 446 in the pragmatic context of Hittite rituals.